A Comparative Study on Syntax in English and Arabic Languages - Younus Idham, Shebli (Opción, 2020)
The study aims to investigate a comparative study on syntax in English and Arabic languages via comparative qualitative research methods. As a result, Contrast between the syntax of center fronting and clitic-left disengagement, center the communication between the hole methodology and the resumptive procedure, an exemplified in sentences which include both center fronting and clitic left separation. In conclusion, in little and commonplace circumstances, humans could convey utilizing single words and numerous motions, especially when managing different individuals from a similar social gathering (family unit, more distant family, clan, etc.).